2008
DOI: 10.1515/cclm.2008.132
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense capacity in scleroderma patients

Abstract: Lower plasma total antioxidant activity and plasma antioxidant gap in scleroderma patients show that plasma antioxidant defense is deficient in scleroderma patients. As previous studies on this issue are controversial, the decreased erythrocyte superoxide dismutase activity found in the patients in this study needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
0
25
1
Order By: Relevance
“…The TAS value remained low, even when corrected as a function of plasma albumin and uric acid, which is defined as RAS. The RAS values were 0.37 ± 0.09 mmol/L Trolox equivalents, which is low compared to those reported by Miller and Sfrent-Cornateanu et al (0.45 and 0.92 mmol/L Trolox equivalents, respectively) (33,50). A number of studies have thus shown that TAS decreases during aging and that there is a gender-related difference, with higher values for men than for women, which is in agreement with our results (data not show).…”
Section: Variables Total (N = 57) Placebo (N = 12) Rt (N = 17) As (N contrasting
confidence: 62%
“…The TAS value remained low, even when corrected as a function of plasma albumin and uric acid, which is defined as RAS. The RAS values were 0.37 ± 0.09 mmol/L Trolox equivalents, which is low compared to those reported by Miller and Sfrent-Cornateanu et al (0.45 and 0.92 mmol/L Trolox equivalents, respectively) (33,50). A number of studies have thus shown that TAS decreases during aging and that there is a gender-related difference, with higher values for men than for women, which is in agreement with our results (data not show).…”
Section: Variables Total (N = 57) Placebo (N = 12) Rt (N = 17) As (N contrasting
confidence: 62%
“…,15,23,32 The plasma components responsible for the antioxidant status are albumin, uric acid, ascorbic acid, a-tocopherol, b-carotene, bilirubin, glutathione, cysteine, dihydrolipoate and ubiquinol. TAC is modulated by the free radical load, metal concentration and dietary intake of antioxidants and results from the balance between oxidant species and plasma antioxidants.…”
mentioning
confidence: 99%
“…Regarding clinical correlation, there was no influence of age, disease duration, skin score, lung involvement (DLco), or inflammation (ESR) on TAP level. [22]. In both reports, there was no difference observed about TAP levels between dSSc and lSSc patients.…”
Section: Discussionmentioning
confidence: 79%
“…TAP measurement in plasma from SSc patients has been reported with conflicting result [21,22]. In the first paper reported by Italian group, TAP level was not decreased against odds, moreover, it was even higher than in healthy control.…”
Section: Discussionmentioning
confidence: 99%